Fetal gender and gestational age differentially affect PCSK9 levels in intrauterine growth restriction. Issue 1 (December 2016) - Pecks, Ulrich; Rath, Werner; Maass, Nicolai; Berger, Bartlomiej; Lueg, Imke; Farrokh, André; Farrokh, Sabrina; Eckmann-Scholz, Christel
Abstract Background Maternal and fetal Low Density Lipoprotein-Cholesterol (LDL-C) concentrations are compromised in intrauterine growth restriction (IUGR). Generally, LDL-C catabolism is under control of PCSK9 by binding to the LDL-receptor leading to its degradation. Hence, we hypothesized a role for PCSK9 in the modulation of lipid metabolism and placental transport in IUGR. Methods 172 women, 70 IUGR and 102 controls were included in the study. Maternal and fetal serum PCSK9 levels and lipid profiles including LDL-C were measured. Placental LDL-receptor and PCSK9 expressions were estimated by tissue microarray immunohistochemistry, and analyzed by two blinded observers using an immunoreactivity score. Non-parametric tests and multivariate regression analyses were used for statistical estimations. Results PCSK9 levels in the maternal and fetal compartment independently predicted LDL-C levels (maternal compartment: adjustedR 2 = 0.2526; coefficientb i = 0.0938, standard error sbi =0.0217, rpartial = 0.4420, t -value = 4.323, p < 0.0001; fetal compartment: adjustedR 2 = 0.2929;b i = 0.1156, sbi =0.020, rpartial = 0.5494, t-value = 5.81, p < 0.0001). We did not find significant differences in maternal PCSK9 concentrations between IUGR and controls. However, we found lower fetal serum PCSK9 concentrations in IUGR than in controls (IUGR median 137.1 ng/mL (95% CI 94.8-160.0) vs. controls 176.8 (154.6-202.5), p = 0.0005). When subgrouping according to early onset, late onset IUGR, and fetal gender differences remained consistent only for male neonates born before 34 weeks of gestation. In the placenta we found no correlation between PCSK9 and LDL-receptor expression patterns. However, the LDL-receptor was significantly upregulated in IUGR when compared to controls (p = 0.0063). Conclusions Our results suggest that PCSK9 play a role in impaired fetal growth by controlling fetal LDL-C metabolism, which seems to be dependent on gestational age and fetal gender. This underlines the need to identify subgroups of IUGR that may benefit from individualized and gender-specific pharmacotherapy in future studies.